2019
DOI: 10.1111/1759-7714.13158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medical thoracoscopy‐guided intrapleural docetaxel therapy to manage malignant pleural effusion in patients with non‐small cell lung cancer: A pilot study

Abstract: Background Although chemical pleurodesis is a useful treatment option for malignant pleural effusion, little is known about the effects of intrapleural docetaxel therapy. Objectives This study aimed to evaluate the effects of medical thoracoscopy‐guided intrapleural docetaxel therapy in patients with lung cancer. Methods Patients with lung cancer who diagnosed malignant pleural effusion were enrolled in this single‐center prospective pilot study. The clinical response and toxicity were evaluated at two, six an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The addition of intrapleural endostatin to standard chemotherapy has shown improved overall response in MPE patients [190]. Preliminary phase I and II trials with intrapleural chemotherapy have shown short-term partial or full response of MPE [191][192][193][194][195][196]. However, these options have not yet to our knowledge been directly compared to standard therapy and further randomised trials are needed.…”
Section: Intrapleural Agentsmentioning
confidence: 99%
“…The addition of intrapleural endostatin to standard chemotherapy has shown improved overall response in MPE patients [190]. Preliminary phase I and II trials with intrapleural chemotherapy have shown short-term partial or full response of MPE [191][192][193][194][195][196]. However, these options have not yet to our knowledge been directly compared to standard therapy and further randomised trials are needed.…”
Section: Intrapleural Agentsmentioning
confidence: 99%
“…Malignant pleural effusion (MPE) is one of the most common adverse consequences of lung cancer in the advanced stages of the disease [ 1 ]. It was reported that MPE is primarily associated with malignant tumors, and lung carcinoma is the most common type [ 2 ].…”
Section: Introductionmentioning
confidence: 99%